Peningkatan Kinerja Melalui Motivasi, Lingkungan Kerja, Kompetensi Dan Kompensasi Pada Hotel XYZ - Tuti Iriani; R. Soni Somali; Indah Sugiarti; M. Abdul Aziz Danu Brata; Mila Karmila (Business Education Program of Universitas Pendidikan Indonesia, 2023)
Human resource management is an approach taken to the abilities, skills, motivation of individuals in an organization with the aim of increasing organizational performance. The phenomena obtained in this study are the factors that influence employee performance, namely work motivation, work environment, competence and compensation. The purpose of this study was to determine and analyze the influence of motivation, work environment, competence and compensation on employee performance. The object under study is XYZ Hotel Employee. The research method used is the census method. The analytical tool used is path analysis. Based on the results of the analysis and discussion adjusted to the problems studied, it can be concluded that the variables of motivation, work environment